A Causal Analysis on Foreign Trade and Economic Growth: The Case of Somalia (International Journal of Scientific Research and Management (IJSRM), 2022)
The relationship between foreign trade and economic growth is one of the most important research areas in the literature. Because the direction and importance of this relationship can vary from country to country and from time to time. In this study, the causal relationship between Somalia’s gross domestic product (GDP), exports and imports for the period 2008-2021 was investigated. Data were obtained from the World Bank database and the website of the Organisation of Islamic Cooperation. For this purpose, whether the series used in the study are stationary or not was investigated by the ADF test and it was determined that all series were integrated at the first level. Johansen Co-integration Analysis was carried out to test the existence of a long-term relationship between the series due to the same level of integration of the series. Here, according to the results of both the trace statistics and the maximum eigenvalue statistics, it is concluded that there is no cointegration vector and it is decided that there is no cointegration relationship between the series. This means that the economy is still not largely dependent on the country’s domestic production, but depends on other factors such as remittances by Somalis living abroad and financial support from the international community, including budget subsidies, development projects and money spent on refugee problems. Keywords: Imports, Exports, Economic Growth, Causality, Var model.